2010
DOI: 10.1063/1.3431024
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous long and short-range ferroelectric ordering in Pb0.55La0.30TiO3 ceramics

Abstract: Bismuth-induced ferroelectric relaxor behavior in paraelectric LaAlO3 J. Appl. Phys. 110, 094107 (2011) Weak-relaxor behaviour in Bi/Yb-doped KNbO3 ceramics Appl. Phys. Lett. 99, 192901 (2011) The effects of polarization dynamics and domain switching energies on field induced phase transformations of perovskite ferroelectrics Appl. Phys. Lett. 99, 162903 (2011) Electrocaloric effect in relaxor ferroelectrics J. Appl. Phys. 110, 074113 (2011) On the phase identity and its thermal evolution of lead f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…Up to now, studies of the LaTiO 3 based systems [9][10][11] are mainly focusing on the aspects of crystal structure, phase, electrical [12], magnetic, and ferroelectric properties. Less work has been done on the optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, studies of the LaTiO 3 based systems [9][10][11] are mainly focusing on the aspects of crystal structure, phase, electrical [12], magnetic, and ferroelectric properties. Less work has been done on the optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In lead-based ferroelectric ceramic systems, the ferroelectric character is directly correlated with the electronic properties of both A-site (Pb 2+ ) and B-site (Ti 4+ ) ions [17,18]. Many studies have shown that the density of states (DOS) of oxygen and titanium atoms could provide a more direct correlation with the ferroelectric stability of perovskite-based compounds [19][20][21][22][23][24][25][26][27][28]. They have also reported a significant modification in the hybridization among O 2p, Pb 6sp and Ti 3d states when the ferroelectric character changes.…”
Section: Introductionmentioning
confidence: 99%
“…In the PLZT and Pb 1Àx Ba x Zr 1Ày Ti y O 3 complex ferroelectric compounds, a reduction in the degree of hybridization between O 2p and Pb 6sp (Ti 3d) states as the amount of La (Ba) increased was directly related to the manifestation of the relaxor character [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…A análise do espectro XANES de uma mesma amostra em função da temperatura mostrou que a estrutura local e a media distância não são afetadas pelos processos de transição de fase observados através das medidas elétricas e de DRX. Estes resultados estão em bom acordo com os observados nas amostras BCZT e como observados em diferentes sistemas cerâmicos apresentando propriedades ferroelétricas(130). Resultados e Discussões Para fins de comparação, amostras de mesma composição foram também sinterizadas a partir do método tradicional em um forno elétrico na temperatura de 1300 o C por 3 horas em ar.Observa-se da Tabela 14 que as amostras sinterizadas pela técnica de SPS apresentam um valor de densidade superior aos das amostras sinterizadas em forno elétrico.…”
unclassified